2013
DOI: 10.2134/agronj2012.0246
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Controlling the Continuous Corn Yield Penalty

Abstract: It is widely accepted that yields decline when corn (Zea mays L.) is grown continuously vs. in rotation with soybean [Glycine max (L.) Merr.], although causes for the yield reduction are unclear. The primary objective of this study was to elucidate the source(s) of the continuous corn yield penalty (CCYP). The experiment was conducted from 2005 to 2010 in east‐central Illinois beginning with third‐year continuous corn (CC) or a soybean–corn (SC) rotation at six N fertilizer rates. Averaged across all years, yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
99
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(114 citation statements)
references
References 44 publications
13
99
2
Order By: Relevance
“…The decrease in the CCYP with higher early and late-season minimum temperatures is also supportive of this, as higher soil temperatures increase soil N mineralization. Contradicting Gentry et al (2013), however, we do not find an increasing CCYP with the number of years continuously cropped. This may be due to differing corn residue management practices used in that study as compared with many commercial farms.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…The decrease in the CCYP with higher early and late-season minimum temperatures is also supportive of this, as higher soil temperatures increase soil N mineralization. Contradicting Gentry et al (2013), however, we do not find an increasing CCYP with the number of years continuously cropped. This may be due to differing corn residue management practices used in that study as compared with many commercial farms.…”
Section: Discussioncontrasting
confidence: 88%
“…This result was consistent with findings by Crookston et al(1991), but not with Gentry et al (2013) who found that CCYP increased with the number of years of continuous cropping. For soybean, the penalty increased with duration of continuous cropping, with differences between 1-and 3-yr, 1-yr and 4-plus yr, and 2-yr and 4-plus yr all being significant, a finding that is also consistent with Crookston et al (1991).…”
Section: Effects By Years Of Continuous Croppingsupporting
confidence: 91%
See 2 more Smart Citations
“…The main reason why corn yield was less in CC than in the other rotations is confounded among the 254 mm of irrigation water applied to corn in CC while corn in the other rotations received 381 mm of irrigation, the obvious differences in the rotations (different crops and sequences), and interaction of the two. A relatively lower corn grain yield in CC vs. other rotations (C-Sb, W-C-Sb, C-Gs-Sb, …) was reported by many other researchers (Schneekloth et al, 1991;Porter et al, 1997;Erickson, 2008;Gentry et al, 2013). However, the 20% less yield that we have reported here for CC is probably mostly due to the difference in irrigation amount.…”
Section: Economic Analysiscontrasting
confidence: 50%